Analisis Pengaruh Jumlah Pengangguran Terhadap Jumlah Kemiskinan Menggunakan Metode Regresi Linier (Studi Kasus: Kota Salatiga) - Mei Irawati; Magdalena A. Ineke Pakereng (Jurnal EMT KITA, 2023)
Poverty continues to be a major global problem, especially in developing countries including Indonesia, the low level of income earned by the community can hinder the welfare and civilization of society to ensure its survival. The purpose of this study was to analyze the effect of the number of unemployed on the amount of poverty based on time series data. The data was obtained from the Central Statistics Agency (BPS) of Salatiga City. This becomes a reference for analyzing the effects of unemployment and poverty in the last 5 years. The method used in this study is the Linear Regression Method. Linear regression is a method to determine how close the relationship or influence is between two variables (independent variables and dependent variables). After conducting research, it showed that the results of the analysis of the effect of the number of unemployed on the number of poverties in Salatiga City using the linear regression method obtained the following regression equation: Y = 8.678123 + 0.0001484 X. Where the variable number of unemployed (X) has a positive effect on the variable the number of poverty (Y) in Salatiga City (b = 0.0001484) but the value of b is almost close to a negative value, therefore it is possible that the number of unemployed can affect the amount of poverty